2022
DOI: 10.1371/journal.pone.0277433
|View full text |Cite
|
Sign up to set email alerts
|

Non-trivial relationship between scaling behavior and the spatial organization of GDP in Indonesian cities

Abstract: Urban scaling analysis has shown that various aggregated urban quantities obey power-law relationships with the population size. Despite the rapid progress, direct empirical evidence that shows how the power-law exponents β depend on the spatial organization of the GDP has been lacking. Moreover, urban scaling studies are hardly reproduced in developing countries due to inadequate official statistics. We tackle these issues by performing urban scaling analysis on Indonesian cities using globally harmonized fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Economic output is found to be higher in high-density built areas as shown by Li [135] who indicated that the urban structures that have evolved from low polycentricity and low dispersion to high polycentricity and low dispersion have undergone the highest per capita GDP growth. A further implication is that of the scaling effect represented by economies of scale and increasing returns, which was found to be stronger for regions with spatially compact GDP distribution, which has been confirmed by Meijers and Burger [136] and Kuno Pradipto [137]. In terms of infrastructure development, it can be asserted that high-density urban development is more effective and economical than lower density development when it comes to the provision of underground utilities (i.e., energy and transport networks, sanitation, etc.…”
Section: Discussionmentioning
confidence: 56%
“…Economic output is found to be higher in high-density built areas as shown by Li [135] who indicated that the urban structures that have evolved from low polycentricity and low dispersion to high polycentricity and low dispersion have undergone the highest per capita GDP growth. A further implication is that of the scaling effect represented by economies of scale and increasing returns, which was found to be stronger for regions with spatially compact GDP distribution, which has been confirmed by Meijers and Burger [136] and Kuno Pradipto [137]. In terms of infrastructure development, it can be asserted that high-density urban development is more effective and economical than lower density development when it comes to the provision of underground utilities (i.e., energy and transport networks, sanitation, etc.…”
Section: Discussionmentioning
confidence: 56%
“…Population growth also contributes to increased energy consumption, which means greater demand for energy services [ 74 ]. The population and GDP relationship is typically positive [ 75 ] where a larger population generally means a more significant labor force, which can produce more goods and services, leading to increased economic output. However, the relationship between these variables and CO 2 emissions is complex and interdependent.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%